2021
DOI: 10.18240/ijo.2021.04.20
|View full text |Cite
|
Sign up to set email alerts
|

Ocular surface changes in Graves’ ophthalmopathy

Abstract: Many patients with Graves' ophthalmopathy (GO) suffer from dry eye syndrome (DES), and this is one of the most common reasons of eye discomfort in patients with GO. The prevalence of DES in patients with GO is significantly higher than normal subjects. The ocular surface changes involving changes in tears, cornea, conjunctiva and glands occur in GO patients. However, the mechanism of how DES occurs in GO still remains unclear. In this review, the ocular surface changes were illustrated and analyzed the reasons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 51 publications
1
13
0
2
Order By: Relevance
“…Hence, in recent years, the proteomic analysis of tear fluids from patients with TAO has been undertaken to better determine disease activity and to stratify patients accordingly, because the high concentration of proteins in tear fluid makes it an important source for studying potential protein biomarkers for GO [ 13 , 33 , 34 ]. Many studies have found several differences in the amount of proteins in active GO, inactive GO, and healthy controls, so we focused on the most recent findings [ 7 ].…”
Section: Markers In the Tears Of Patients With Graves’ Orbitopathymentioning
confidence: 99%
See 2 more Smart Citations
“…Hence, in recent years, the proteomic analysis of tear fluids from patients with TAO has been undertaken to better determine disease activity and to stratify patients accordingly, because the high concentration of proteins in tear fluid makes it an important source for studying potential protein biomarkers for GO [ 13 , 33 , 34 ]. Many studies have found several differences in the amount of proteins in active GO, inactive GO, and healthy controls, so we focused on the most recent findings [ 7 ].…”
Section: Markers In the Tears Of Patients With Graves’ Orbitopathymentioning
confidence: 99%
“…In response to the activation of these receptors by autoantigens, fibroblasts may modulate immune responses via the production of cytokines and extracellular matrix/hyaluronan and elicit an inflammatory reaction in the orbit. The production of glycosaminoglycans (GAGs) by orbital fibroblasts and the hyperplasia of adipose tissue contribute to the development of ocular symptoms such as enlarged extraocular muscles and increased fatty and connective tissue, resulting in protruding eyes, double vision, and in severe cases, visual field loss or even loss of vision [ 1 , 4 , 6 , 7 , 8 , 9 ]. The symptoms of GO are primarily due to inflammation, and the severity of GO is categorized as mild, moderate, and severe (including sight-threatening) [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In GO patients, the evaporation of tears may be caused by long-term ocular exposure because of eyelid retraction and proptosis ( 5 ). Studies have shown that lacrimal glands in GO patients are involved in autoimmune responses, leading to changes in the composition of tears ( 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…Dry eye is one of the most common symptoms in TAO patients (Sun et al, 2021) [ 5 ]. A total of 65–85% of TAO patients are found to have complaints of dry eye symptoms (Selter et al, 2015) [ 6 ].…”
Section: Introductionmentioning
confidence: 99%